A test of work motivation profile similarity across four distinct samples of employees. Issue 4 (20th June 2020) - Gillet, Nicolas; Morin, Alexandre J.S.; Ndiaye, Adama; Colombat, Philippe; Fouquereau, Evelyne
Abstract : The present study examines how the different forms of behavioural regulation proposed by self‐determination theory combine within different profiles of workers and the extent to which these configurations are replicated among four samples of workers from distinct occupational groups (managers, nurses, physiotherapists, and hospital employees). In addition, this research investigates the role of workload (as a job demand), as well as perceived organizational, supervisor, and colleagues support (as job resources) in the prediction of profile membership. Finally, this research also documents the relation between motivation profiles and a series of adaptive (work performance) and maladaptive (presenteeism, turnover intentions, and absenteeism) work outcomes. Latent profile analyses revealed six similar motivation profiles among the four samples (n = 291 managers, 249 hospital employees, 237 nurses, and 373 physiotherapists). The results also showed the highest levels of presenteeism and turnover intentions, and the lowest levels of work performance to be associated with the Externally Driven profile. Moreover, workload predicted a higher likelihood of membership into the Self‐Driven Introjected and Externally Driven profiles relative to the Moderately Intrinsically Motivated, Highly Intrinsically Motivated, and Self‐Driven Hedonist profiles. Finally, perceived colleagues support predicted a decreased likelihood of membership into the Externally Driven profile relative to the five other profiles, whereas higher levels of perceived organizational support predicted an increased likelihood of membership into the Self‐Driven Introjected, Highly Intrinsically Motivated, and Value‐Reward Self‐Driven profiles relative to the Externally Driven and Self‐Driven Hedonist ones. Practitioner points: Employees' profiles characterized by low levels of self‐determined work motivation were associated with the worst outcomes. By decreasing employees' workload or by helping to make it more manageable, organizations may increase employees' likelihood of displaying more desirable, and self‐determined, motivational profiles. By improving colleagues support, organizations may also be able to increase employees' likelihood of displaying more desirable, and self‐determined, motivational profiles.